2019
DOI: 10.1136/bmjopen-2018-023647
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with premature myocardial infarction: a systematic review protocol

Abstract: IntroductionPremature myocardial infarction (MI) generally refers to MI in men ≤55 years or women ≤65 years. Premature MI is a major contributor to cardiovascular disease (CVD), which claimed 17.6 million lives globally in 2016. Reducing premature MI and CVD is a key priority for all nations; however, there is sparse synthesis of information on risk factors associated with premature MI. To address this knowledge gap, we are conducting a systematic review to describe the association between risk factors (demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Two researchers independently extracted the data, and any discrepancy was resolved by discussion. The quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS) independently by two researchers [19].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Two researchers independently extracted the data, and any discrepancy was resolved by discussion. The quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS) independently by two researchers [19].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…The study protocol (PROSPERO: CRD420 18076862) has been described. 24 This study is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines (Supplemental Table 1, available online at http://www.mcpiqojournal.org). 25,26…”
Section: Methodsmentioning
confidence: 99%
“…An LCA model was built using 11 known and proposed risk factors for CHD as binary variables: cigarette smoking, obesity, diabetes, family history of CHD, alcohol consumption, opium addiction, hypertension, PVD, HLP, history of stroke, and MI. The included risk factors were added to the statistical model based on premature systematic review studies ( 24 , 25 ). The LCA analyses were conducted using the “poLCA” package in R 3.4.2.…”
Section: Methodsmentioning
confidence: 99%